Highlights From the Annual Meeting of the American Epilepsy Society 2018. Issue 3 (May 2019) - Jobst, Barbara C.; Ben-Menachem, Elinor; Chapman, Kevin E.; Fu, Aradia; Goldman, Alica; Hirsch, Lawrence J.; Jehi, Lara E.; Kossoff, Eric H.; Plueger, Madona; Rho, Jong M.; Schevon, Catherine A.; Shinnar, Shlomo; et al.
The American Epilepsy Society Meeting in New Orleans attracted more than 5900 attendees. There was a lively exchange of new science, innovation, education, clinical practice, and many other items related to epilepsy. Educational symposia were a major part of the meeting and explored varying topics of interest for all types of epilepsy professionals. This article reviews highlights of the meeting presented in major symposia. Topics ranged from how to treat varying aspects of epilepsy as a consultant in the hospital to finding the scientific underpinning of the interaction between sleep and epilepsy. Pros and cons of novel antiseizure medications, dietary, and stimulation treatments were discussed. Epilepsy may impair memory and we need to learn what is the pathophysiologic relationship. Febrile status epilepticus may have severe consequences for a later life with seizures. Epilepsy professionals should be very well aware of the ethical implications of devasting seizures and their associated disability. These are just a few select topics of the many that we need to study further to archive the final goal to improve the lives of patients with epilepsy.